Tofacitinib in Hypertrophic Lichen Planus - Peter Seiringer; Felix Lauffer; Anna Caroline Pilz; Danielle Boehmer; Tilo Biedermann; Kilian Eyerich (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)